UTILIZING DIGITAL LEARNING RESOURCES IN ENGLISH-SPECIFIC PURPOSES LEARNING CLASSROOM: ESP TEACHERS’ PERSPECTIVES - Imam - Fauzi; Yudi - Juniardi; Wahyudin - - (Globish: An English-Indonesian Journal for English, Education, and Culture, 2023)
Nowadays, the development of technology has significantly affected how ESP teachers deliver their learning materials in the language classroom. This study aims to reveal the perceptions of ESP teachers towards digital learning technology devices used, both inside and outside the classroom. There are 25 ESP teachers of Serang Raya University engaged in this research. By using a questionnaire through Google Forms, this research revealed that although some students understand the importance of using digital devices in teaching practice in the classroom, they admit that their use has not been maximized due to their lack of knowledge about digital learning media.